An account of the real-life hepatitis C management in a single specialized viral hepatitis treatment centre in Egypt: results of treating 7042 patients with 7 different direct acting antiviral regimens. (2nd December 2018) - El Kassas, Mohamed; Alboraie, Mohamed; Omran, Dalia; Salaheldin, Mohamed; Wifi, Mohamed Naguib; ElBadry, Mohamed; El Tahan, Adel; Ezzat, Sameera; Moaz, Enass; Farid, Amir M; Omar, Heba; Abouelkhair, Mahmoud; et al.
ABSTRACT: Background : A large Egyptian treatment program for HCV was launched in2014 after the introduction of direct-acting antiviral agents (DAAs). This program depended mainly on establishing specialized independent centres for HCV treatment. These centres represent the major strengths in the Egyptian model of care, as they provide integrated care for HCV patients and have enabled Egypt to treat more than one million patients in 3 years. The New Cairo Viral Hepatitis Treatment Center (NCVHTC) is an example of these specialized centres. Methods : The Egyptian experience in the management of HCV was evaluated by analysing the data of real-life HCV management in the NCVHTC from 2014 to 2017. Results of different treatment regimens in addition to their strengths, limitations and areas for improvement are discussed in this report. Results : A total of 7042 HCV patients have been evaluated for treatment in the NCVHTC. Among them, 5517 patients received treatment by seven different DAA regimens with excellent results. Conclusions : All regimens were highly effective at treating HCV in a real-life setting, apart from SOF/RBV, which was the least effective. A nationwide screening program and enhancing the follow-up of treated patients are the main missing pillars in the Egyptian model.